THE HISTORICAL OVERVIEW OF QUAKE MANAGEMENT POLICY IN CHINA: FROM TANGSHAN, SICHUAN, TO YUNNAN - Devi Riskianingrum (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2015)
The earthquake is one of the deadliest natural disasters that hinder economic progress in China. The two biggest 20th century catastrophic quakes occurred in China are Tangshan in 1976 and Sichuan in 2008. Additionally, there are at least four massive earthquakes that struck China in the last five years. Hence, the disaster management is one of the main factor to be seriously administered by the Chinese government, both in the central level as well as to the regional and local level. Therefore, this paper aims to examine some policies issued by the Chinese government in the context of earthquake management and its effectiveness. The discussions on disaster management in China have been deeply explored by Asia Pacific Research Team at The Research Center for Regional Resources LIPI and published under the title of Disaster Management in China: History and Institutional Networks in 2010.Furthermore, the research team also conducted a research on the Sichuan earthquake and published a monograph entitled The Representation of Sichuan Earthquake: State Control, Museum, and The Role of the Army. We conduct both some in-depth interview and literature review concerning the historical process of initiating some earthquake policies, and its practical effectiveness. This paper discusses the disaster management based on various policiesand responses of two contemporary deadliest quake in Tangshan (1976) and Sichuan (2008), and two recent earthquakes occurred in Qinghai (2010) and Yunnan (2014). The paper claims that policies and regulations issued by the government in disaster management in China are successful to some extent though there is a lack of coordination, and some informational gaps in the existing institutions.Keywords: Tangshan earthquake, Sichuan earthquake, disaster management, China.